1999
DOI: 10.1180/002646199548394
|View full text |Cite
|
Sign up to set email alerts
|

Defect structure and luminescence behaviour of agate — results of electron paramagnetic resonance (EPR) and cathodoluminescence (CL) studies

Abstract: Generally, the abundance of 03 centres (silicon vacancy) and E'I centres (oxygen vacancy) in agate is remarkably higher than in quartz. The high defect density in agates points to rapid growth of silica from a strongly supersaturated solution probably with a noncrystalline precursor.CL microscopy reveals internal structures and zoning in agates and quartz incrustations which clearly differ from those discernible by conventional polarizing microscopy. The CL spectra of agates differ from those of quartz from cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 24 publications
1
73
0
1
Order By: Relevance
“…A red emission at around 670 nm in the synthetic enstatite is assigned to an impurity center derived from activated Mn 2+ substituted for Mg as an electron transition of 4 T 1g (G) → 6 A 1g (S) (Catalano et al, 2014). This electron transition similar to those in olivine and calcite is affected by the crystal field of the ligant oxygens coordi- nated to the host Mn ion (Marfunin, 1979;Götze et al, 1999). Lofgren and DeHart (1992) confirmed that synthetic enstatite without impurities of Mn and Cr emits blue CL, suggesting other emission centers not related to impurity centers.…”
Section: +mentioning
confidence: 99%
“…A red emission at around 670 nm in the synthetic enstatite is assigned to an impurity center derived from activated Mn 2+ substituted for Mg as an electron transition of 4 T 1g (G) → 6 A 1g (S) (Catalano et al, 2014). This electron transition similar to those in olivine and calcite is affected by the crystal field of the ligant oxygens coordi- nated to the host Mn ion (Marfunin, 1979;Götze et al, 1999). Lofgren and DeHart (1992) confirmed that synthetic enstatite without impurities of Mn and Cr emits blue CL, suggesting other emission centers not related to impurity centers.…”
Section: +mentioning
confidence: 99%
“…Lasting less than 30 s, the yellow CL shifts to reddish violet, similar to the final color observed in the quartz grains. Götze et al [1999] detected yellow (580 nm) CL emission in agates and hydrothermal vein quartz, which they associated with high concentrations of lattice defects, primarily E 1 centers (oxygen vacancies). Lattice defects are extremely common in these types of quartz, a result of rapid silica growth from strongly supersaturated solutions, in some cases with a noncrystalline precursor [Götze et al, 1999].…”
Section: Matagami Vms Orementioning
confidence: 99%
“…Götze et al [1999] detected yellow (580 nm) CL emission in agates and hydrothermal vein quartz, which they associated with high concentrations of lattice defects, primarily E 1 centers (oxygen vacancies). Lattice defects are extremely common in these types of quartz, a result of rapid silica growth from strongly supersaturated solutions, in some cases with a noncrystalline precursor [Götze et al, 1999]. The transient bright yellow CL associated with quartz microcracks and grain boundary fillings clearly documents secondary hydrothermal infiltration through the original massive sulfide mounds.…”
Section: Matagami Vms Orementioning
confidence: 99%
See 1 more Smart Citation
“…With the recent development of scientific tools many advanced researches are conducted to understand the physical natures of quartz. Agrosì et al (1992), Rink et al (1993), Onasch and Vennemann (1995), Stevens Kalceff and Phillips (1995), Carpenter et al (1998a), Götze et al (2001), Botis et al (2005) and Götze et al (2005) focused on different physical characteristics of quartz and its importance as a natural compound. Considering the physical importance of quartz in material and earth sciences we decided to perform an experiment on imaging for visualising nanomorphological characteristics or surface geometry this mineral by digital imaging.…”
Section: Introductionmentioning
confidence: 99%